Um panorama sobre a gestão e gerenciamento de resíduos químicos em algumas Universidades Brasileiras - Carvalho, Lorys (Universidade Federal de São Carlos, 2023)
The theme, chemical residues, has been much discussed in recent years, mainly due to the environmental issue, causing several institutions moving to solve problems with their passive and active residues, which in large part have been stored for many years, causing storage and security issues. Some universities have been concerned with these problems for some years, so they have put into practice a Chemical Residues Management Plan, with the intention of standardizing and improving management of waste in the generating units, worrying from segregation to the correct final destination. The present work brings a systematic bibliographic review on the management of chemical waste in 40 Brazilian Universities in order to compare and identify which Universities have or do not have information about the management of their chemical waste. It is noted that only 8 institutions presented some PGRS/PGRQ document, so it is possible to observe that the topic is still little discussed or treated in a concrete way within Brazilian Universities.
An overview of the management and administration of chemical waste in some Universities Brazilian
Keywords: Resíduos químicos; Plano de gerenciamento de resíduos químicos; Chemical residues; Chemical residues management plan; CIENCIAS EXATAS E DA TERRA::QUIMICA